2018
DOI: 10.1007/978-1-4939-8559-3_20
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Modified Collagen-Induced Arthritis Mouse Model to Investigate the Anti-inflammatory Activity of Progranulin in Inflammatory Arthritis

Abstract: Progranulin (PGRN) was found to play an anti-inflammatory and protective role in both inflammatory and degenerative arthritis (Tang et al., Science 332:478-484, 2011; Zhao et al., Ann Rheum Dis 74:2244-2253, 2015). We recently published a visualized protocol to demonstrate a surgically-induced mouse model for examining the protective role of PGRN in degenerative osteoarthritis (Zhao et al., J Vis Exp:e50924, 2014). Herein we describe a modified collagen-induced arthritis (CIA) mouse model to investigate the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The suppression of YAP in Pdk1 knockout mice may maintain the number of primordial follicles compared with the vehicle control, indicating that YAP plays an essential role in regulating POF. The expression of the core components of Hippo pathway was altered with follicle development, and the trend of this alteration was consistent with that in follicles cultured in vitro in a recent study (19). Primordial follicle activation was accompanied by the attenuation of the Hippo pathway, therefore suggesting a close association of the Hippo pathway and primordial-to-primary transition.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The suppression of YAP in Pdk1 knockout mice may maintain the number of primordial follicles compared with the vehicle control, indicating that YAP plays an essential role in regulating POF. The expression of the core components of Hippo pathway was altered with follicle development, and the trend of this alteration was consistent with that in follicles cultured in vitro in a recent study (19). Primordial follicle activation was accompanied by the attenuation of the Hippo pathway, therefore suggesting a close association of the Hippo pathway and primordial-to-primary transition.…”
Section: Discussionsupporting
confidence: 87%
“…A mixture of 0.75 ml ketamine (150 mg/kg) and 0.25 ml xylazine (10 mg/kg) was prepared and diluted to 5 ml with sterile 1X PBS (19). Mice (20 g) were administered a 0.125 ml mixture for anesthesia via i.p.…”
Section: Serum Analysismentioning
confidence: 99%
“…Tang et al demonstrated that rPGRN and Atsttrin, an engineered PGRN derivative containing the minimal TNFR binding motifs, significantly alleviated the disease severity in collagen antibody-induced, collagen-induced and TNF-α transgenic inflammatory arthritis mouse models [7,48,49,81]. Both agents effectively inhibited the progression of inflammatory arthritis, and inflammatory phenotypes returned following the cessation of Atsttrin treatment [7].…”
Section: Pgrn Targeting In Autoimmune and Inflammatory Diseases 41 Inflammatory Arthritismentioning
confidence: 99%
“…Additionally, PGRN is important for chondrocyte proliferation and differentiation, which are functions recapitulated in animal models of cartilage defect (Feng et al, 2010;Kong et al, 2016). Recent studies reported that PGRN and its engineered derivative Atsttrin demonstrated a therapeutic effect in inflammatory and degenerative arthritis murine models through binding to tumor necrosis factor receptors (TNFRs) (Tang et al, 2011;Wei et al, 2017;Wei and Liu, 2018). Atsttrin, comprising half-units of granulins A, C, and F plus linkers P3, P4, and P5, lacks the oncogenic activity of PGRN.…”
Section: Introductionmentioning
confidence: 99%